PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Pembeli dan Pengguna Honda Beat Series di Astra Honda Motor Gajahmada Semarang) - Yoannes Tito; Agung Budiatmo (Universitas Diponegoro, 2017)
products with various advantages. One of the automotive products that often discussed is hondabeat series. To face up fierce business competition honda beat series needs to influenceconsumers to choose and buy products honda beat series. Many factors affect consumers inmaking purchases, including Product Quality and Promotion. This study aims to determine thequality of products and promotion for product purchase decision of honda beat series partiallyand simultaneously. This type of research is explanatory research.The questionnaire primary data is used and distributed to Semarang people who decided to buyand use honda beat series at astra honda motor gajahmada semarang dealer, counted as many as100 people. In the analysis used validity and reliability, correlation coefficient, coefficient ofdetermination, simple and multiple regression analysis, and significance test (t test and F test)using SPSS 22.The result of this study showed that the contribution given by product's quality (X1) towardbuying decision (Y) is 9.6%. The contribution given by promotion (X2) toward buying decision(Y) is 23.9%. The contribution given by product's quality (X1) and promotion (X2) towardbuying decision (Y) is 24.1%. From the two variables that affect buying decision, promotion isthe most significant variable that affects the customer's decision to buy Honda Beat Series.